Restricting Child Factory Labour In Late Nineteenth Century Ontario - Hurl, Lorna (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1988)
Abstract This paper investigates the changing experience of child factory labour in late 19th and early 20th century Ontario. It explores the largely accepted, though untested assumptions that restrictive legislation (the Ontario Factory Act of 1884) was achieved at the behest of middle and upper-class social reformers whose concern was motivated by a new concept of childhood. The evidence provided reveals that, contrary to historical myth, organized labour was the motivating force behind the anti-child labour legislation. It also indicates that, once proclaimed, the legislation was poorly monitored and enforced and, as such, was largely ineffective in curtailing the practice of child labour. Despite this, however, the paper provides evidence to show that child factory labour did decline significantly after the mid-1890s. The explanation offered is essentially one of changes in the demand for and the supply of child labor. That is, the centralization and accumulation of industrial capital in concert with technological advances in production restricted opportunities for child factory labor. At the same time, improvements in workers' standards of living reduced the need for families to send children to work. The study does not deny the importance of the changing concept of childhood in curtailing child labour. However, rather than being afforded primacy, the new views of childhood are seen as part of the social backdrop which made employers of children subject to criticism and adult workers desirous of protecting children's 'tender years'.